Desarrollo gonadal y ciclo reproductivo de Lutjanus peru (Pisces: Lutjanidae) en Guerrero, México - Santamaría-Miranda, Apolinar (2003)
In this paper, aspects of the reproductive biology of Lutjanus peru that can be used for the fishery management are described. Samples were taken monthly in 1993 and 1994, from commercial catches in the southern coast of Guerrero, Mexico. A global sex ratio of 1:1.37 (M:F) was found, but the sex ratio was highly variable each month. The condition factor, gonadosomatic, hepatosomatic and stomach fullness indexes were analyzed. None of the morphophysiological indexes showed any clear tendency. From 377 gonads, both male and female, five developmental stages were characterized for each sex. L. peru shows asynchronous gonad development and multiple spawning. Two spawning period were observed in 1993 (March, and August- September) and three in 1994 (April-May, July-August, and November), with a maximun in August of both years. Length at first maturity for the females of L. peru was estimated at 295 mm fork length